An integrated framework for customer loyalty in the hotel sector - Tabaku, Elvira; Kruja, Drita (Serbian Journal of Management, 2019)
This study explores the impact of the antecedents (i.e., service quality, image, trust, perceived value and customer satisfaction) on customer loyalty in the hotel sector. A total of 361 valid responses from a survey conducted in Albania were received. Data were analyzed using exploratory and confirmatory factor analysis and structural equation modeling. Findings suggest that service quality, image, trust, perceived value and customer satisfaction are reliable predictors of customer loyalty in the hotel sector.The results of this study can help and guide practitioners in understanding significant elements of their offer toward loyalty creation and reinforcement.